Influence of solar radiation on dry matter accumulation of fodder plantain (Plantago Lanceolata L.) - Ortiz Pantoja, Yosselyn Mabel; Mier Quiroz , Maritza de los Ángeles (SATHIRI, 2025)
Solar radiation directly influences the accumulation of dry matter, but it is also crucial to determine the optimum moment to take advantage of the nutritional content of pastures. In the case of fodder plantain (Plantago lanceolata L.), it is recommended to use it when it reaches 6 to 7 true leaves, establishing between 7 to 10 days, as opposed to white clover, which does so in 10 to 12 days. It is important to consider that mature plants tend to accumulate anti-nutritional compounds, such as tannins, which reduce their palatability and digestibility, in addition to contributing to greenhouse gas emissions. Climate change also reduces growing seasons, affecting pasture quality. This research aims to evaluate, through a documentary analysis, the accumulation of dry matter, protein and energy in forage plantain, considering climatic variables such as solar radiation, relative humidity and precipitation. The objective of this research is to evaluate, through a documentary analysis, the accumulation of dry matter, protein and energy in fodder plantain, considering climatic variables such as solar radiation, relative humidity and precipitation. A methodology based on literature review of scientific articles published between 2015 and 2025, from databases such as Scopus, ScienceDirect and Web of Science was used, focusing the search on producing countries. The results showed that Colombia presented the most balanced data (3750 kg/ha DM, 153.62 kWh/m² of radiation, 77 % relative humidity and 3240 mm of precipitation), concluding that fodder plantain is a resilient and efficient species in diverse climatic conditions, with a higher productive potential in areas with radiation of 150-200 kWh/m² and precipitation between 1000 and 3000 mm, conditions similar to those of Ecuador.
Keywords: climate change; sustainability; forage production; biomass